Handbook of muscle variations and anomalies in humans : a compendium for medical education, physicians, surgeons, anthropologists, anatomists, and biologists /: a compendium for medical education, physicians, surgeons, anthropologists, anatomists, and biologists. (2022) - Boyle, Eve K
No abstract available